2018
DOI: 10.1007/s10103-018-2607-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the percentage of air/water in spray on the efficiency of tooth ablation with erbium, chromium: yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser irradiation

Abstract: We aimed at examining the effects of a percentage of air/water in spray on the cutting efficiency of Er,Cr:YSGG laser for enamel and dentin. The intensity and frequency of irradiation were 3.0 W and 20 Hz for the enamel surface and 2.0 W and 20 Hz for the dentin surface, respectively. Flattened surfaces of enamel and dentin were irradiated at nine points for approximately 1 s under various percentages of air/water in spray using Er,Cr:YSGG laser. A high-speed video microscope was used to record each laser irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Therefore, in this study, the power setting of 4.5 W was used to prevent overheating and other unwanted effects on dental tissue, and also, air percentage was chosen as 50% as the previous study by Shinkai et al . [21] concluded that lower percentage of air has a better dentin-cutting efficacy than higher percentage of air, when the percentage of air was between 50% and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, the power setting of 4.5 W was used to prevent overheating and other unwanted effects on dental tissue, and also, air percentage was chosen as 50% as the previous study by Shinkai et al . [21] concluded that lower percentage of air has a better dentin-cutting efficacy than higher percentage of air, when the percentage of air was between 50% and 70%.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zach and Cohen (1) , a 5.5°C temperature increase could cause pulp necrosis in 15% of teeth, thus the laser was applied with water-cooling in the present study to reduce the probability of intra-pulpal temperature increase while debonding the ceramic brackets. Shinkai et al (25) stated that a spray with 70% water was the most efficient. They also showed that shallow ablation of dentin was optimized with a spray with 70% air.…”
Section: Debonding Proceduresmentioning
confidence: 99%
“…Hopefully, in other fields, the water jet drilling technique will become increasingly mature. Colliding water jet is a case in which the water jet drilling technique can drill accurately and safely [44,45].…”
Section: Plos Onementioning
confidence: 99%